THE GROWTH OF BLACK PEPPER CUTTING AS EFFECT OF SHADING AND AUXIN - Handayani, Eni (Fakultas Pertanian Universitas Tanjungpura, 2020)
One of the successfull of black pepper production is influenced by the use of healthy and good black pepper seedling quality. The research aims to obtain the best combination of the use of growth hormone origin with the intensity of shade on the success rate and growth of pepper cuttings. The study was conducted in jerora village I Sintang district. The study was conducted in August-December 2018. The research was conducted using two factors with the split plot model research design. The main plot is a shade consisting of 2 levels (n1 = 25% shade and n2 = 75% shade) and subplot is an auxin hormone consisting of ho = control, h1 = 1% synthetic IAA, h2 = shallot extract and h3 = Sprout Extract. The results showed that the percentage of cutting growth in paranet shade was 75% higher with paranet usage 25%. The average number of leaves using natural auxin hormone derived from onions shows the highest number of leaves, 9 strands. The highest plant height is shown in the shade treatment of 75% which is 18.7 cm. In the root dry weight variable the best combination treatment was shown in the use of the origin of the natural auxin hormone derived from the sprouts and 75% shade extract of root dry weight 0.42 g, and root shoot ratio 0, 61%Keywords: IAA, shallot extract, bean sprout extract.